The Problems of Realizing the Innovative Potential of Science and Mechanisms for their Solution - Ianchenko Zinayida B. (Problemi Ekonomiki, 2017)
The aim of the article is revealing reasons for the low payoff of science in terms of the effectiveness of the research activity and demand for its results in economic spheres, identifying problems in the innovation activity of research institutions and reasons for their arising, searching for fundamental approaches to the development of a strategy and mechanisms for realization of the innovative potential of science to strengthen its position in the real sector. The study used general scientific methods, including: systems approach — to systematize the problems of the innovation activity of research institutions; methods of theoretical generalization — to study the theoretical principles of the scientific and innovation activity; methods of analysis and synthesis — to search for fundamental approaches to the development of mechanisms for realization of the innovative potential of science. The used concepts of scientific activity and innovations are generalized. The author’s definition of the term “innovation” is proposed. The main reasons of the minor impact of science on the economy are systematized, the mechanisms for their elimination are offered. Based on the comprehensive analysis of the reasons for losing by science its impact on the economy, the ways of realizing the innovative potential of science are improved. The results of the research can be used in reforming domestic scientific research institutions.